IN VITRO PHYTOREMEDIATION OF PERSISTENT ORGANIC POLLUTANTS BY Helianthus annuus L. PLANTS - Almeida, Marcos V. de; Rissato, Sandra R. [UNESP]; Galhiane, Mario S. [UNESP]; Fernandes, Joao R. [UNESP]; Lodi, Paulo C. [UNESP]; Campos, Marcelo C. de (Soc Brasileira Quimica, 2018)
Plant model systems are needed to properly conduct basic laboratory studies prior to field applications of phytoremediation. In vitro plant cultures are a useful tool for such research. This study focuses on the removal and/or degradation of 24 persistent organic pollutants under in vitro conditions by Helianthus annuus L (sunflower). The main purpose of exploiting this plant for phytoremediation process is due to its strong adaptability to adverse environments conditions such as resistance to pests, disease, and others. The study of bioremediation effects of all chemical molecules under in vitro conditions showed promising results. Sixteen out of twenty-four compounds evaluated reached up to 87% for remediation. The highest accumulation of pollutants was observed in the roots, showing that these results are consistent with the current literature. Through the study, it was observed effective absorption of POPs with logK(ow) ranging from 4.50 to 6.91. Sunflower phytoremediation process efficiently detected heptachlor, aldrin, heptachlor epoxide, trans-chlordane, chlordane, dieldrin, DDE, DDT, methoxychlor, mirex and decachlorobiphenyl.
Keywords: phytoremediation; Helianthus annuus L; POPs